IDENTIDAD CULTURAL Y MESTIZAJE COMO REFLEJO DE LA GESTIÃ“N ADMINISTRATIVA EN CIUDAD JUÃREZ CHIHUAHUA - Arellano, Armando; Cardona, Nicolás; Contreras, Tomás Cuevas; Lucero, Manuel (European Scientific Journal, ESJ, 2015)
Cultural identity has been tried to be conceptualize from different thesis, one of which has had the greatest influence is the Miscegenation The paper presents this process of miscegenation from the general to the particular, starting with Mexico and giving a focus to the North region Mexico, contextualizing the influence of this thesis in different social phenomena, as reflected in the Administrative and their relationships between elements that distinguish this thesis as the best that explains the cultural identity of Ciudad Juarez, as a result of meeting this evolution of cultures and US influence in the region at the border.